2000
DOI: 10.1007/s002100000242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training on functional activity of 5-HT 1B receptors in rat central nervous system: role of 5-HT-moduline

Abstract: The effect of physical exercise was examined on the sensitivity of 5-HT1B receptors and on 5-HT-moduline tissue concentration in the central nervous system of rats. Rats were trained for 7 consecutive weeks to run on a treadmill. Three groups of animals were selected: group 1, sedentary rats (controls); group 2, animals running for 1 h at 18 m/min for 5 days per week (moderate training) and group 3, animals running for 2 h, at 30 m/min on a 7% grade for 5 days per week (intensive training). The animals were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…An alternative possibility is that 5-HT 1B receptors expressed in motoneurons presynaptically control transmitter release at the motor plate level (D'Agostino et al, 2006). Broadly supportive of this are the findings that 5-HT 1B receptor expression declines in the brain in response to physical training (Chennaoui et al, 2000). There is also evidence that 5-HT 1B receptors carry trophic and other signals during embryonic and postnatal development both in the brain and peripheral nervous system (Nebigil et al, 2001).…”
Section: Development Of Aminergic Control Of Respiratory-modulatedmentioning
confidence: 79%
“…An alternative possibility is that 5-HT 1B receptors expressed in motoneurons presynaptically control transmitter release at the motor plate level (D'Agostino et al, 2006). Broadly supportive of this are the findings that 5-HT 1B receptor expression declines in the brain in response to physical training (Chennaoui et al, 2000). There is also evidence that 5-HT 1B receptors carry trophic and other signals during embryonic and postnatal development both in the brain and peripheral nervous system (Nebigil et al, 2001).…”
Section: Development Of Aminergic Control Of Respiratory-modulatedmentioning
confidence: 79%
“…Four weeks of moderate treadmill exercise decreases the levels of 5-HT without affecting the metabolism of 5-HT in the hippocampus [111]. On the contrary, seven days of high-intensity treadmill exercise significantly increases the levels of hippocampal 5-HT [112]. Furthermore, four-week moderate treadmill exercise does not change 5-HT concentration in the amygdala [111].…”
Section: Exercise Modulates the Activities Of Da Ne And 5-ht Systemsmentioning
confidence: 99%
“…Maternal separation-induced depression-like behaviors and elevation of the hippocampal 5HT 1A receptor levels can be recovered by chronic wheel running [115]. Elevated levels of 5-HT 1B receptor activity in the hippocampus have been reported in rats subjected to one week of moderate treadmill exercise [112]. Higher levels of 5-HT 1B receptor in the hippocampus have been associated with resistance to electric stimulation-elicited learned helplessness [116].…”
Section: Exercise Modulates the Activities Of Da Ne And 5-ht Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, investigators have already shown that exercise alters the function of the nervous system at multiple levels by influencing gene expression (Cotman & Berchtold, 2002;O'Neal, Van Hoomissen, Holmes, & Dishman, 2001), protein synthesis (Eilam, Pinkas-Kramarski, Ratzkin, Segal, & Yarden, 1998;Gomez-Pinilla, Ying, Roy, Molteni, & Edgerton, 2002;Gomez-Pinilla, Ying, Opazo, Roy, & Edgerton, 2001;Irwin et al, 2000), cellular metabolism (McCloskey, Adamo, & Anderson, 2001), neuronal firing rate (Jacobs & Fornal, 1999;Rasmussen, Morilak, & Jacobs, 1986), neurotransmitter level (Dunn, Reigle, Youngstdet, Armstrong, & Dishman, 1996) and release (Meeusen, Piacentini, & DeMeirleir, 2001;Soares et al, 1999), receptor level (Yoo, Tackett, Crabbe, Bunnell, & Dishman, 2000), receptor function (Chennaoui et al, 2000), and CNS morphological characteristics (Churchill et al, 2002). The answer to this question is multifaceted and depends upon what level of CNS function is of interest.…”
Section: Exercise Neuroscience: Current Knowledgementioning
confidence: 99%